A GDI/GDF-like system for sorting and shuttling ciliary proteins. (2nd October 2017) - Ismail, Shehab
ABSTRACT: Post/co-translational modifications by the addition of lipids take place in a vast number of proteins. Rab and Rho are small G proteins which are prenylated and targeted to membranes in complex with solubilizing factors called guanosine dissociation inhibitors (GDIs). The release of Rab and Rho at the correct destination from their cognate GDI has been proposed to be mediated through GDI displacement factors. However this mechanism is yet to be established and it has been shown that loading of Rab proteins with GTP at the destination can be sufficient for their correct targeting. PDE6D shares structural homology with Rho GDI and solubilises several prenylated proteins and mediate their targeting to different destinations including cilia. In a paper published by Fansa et al, the authors propose that sorting of cargo is dependent on the differential release by bona fide GDFs, Arl2 and Arl3, and the localization of the active Arl3GTP in cilia.